Long-term neurodevelopmental outcome after prenatal exposure to maternal hematological malignancies with or without cytotoxic treatment. Issue 6 (18th August 2021) - van Gerwen, Mathilde; Huis in 't Veld, Evangeline; van Grotel, Martine; van den Heuvel-Eibrink, Marry M.; Van Calsteren, Kristel; Maggen, Charlotte; Drochytek, Vit; Scarfone, Giovanna; Fontana, Camilla; Fruscio, Robert; Cardonick, Elyce; van Dijk-Lokkart, Elisabeth M.; et al.
ABSTRACT: Data on the long-term neurodevelopmental outcomes of children exposed to hematological maternal cancer with or without treatment during pregnancy are lacking. A total of 57 children, of whom 33 males and 24 females, prenatally exposed to hematological malignancies and its treatment, were invited for neuropsychological and physical examinations at 18 months, 36 months, 6, 9, 12, 15 and 18 years of age. Oncological, obstetrical, neonatal and follow-up data of these children were collected. Parents were asked to complete questionnaires on their child's general health, school performances, social situation, behavioral development, executive functioning, and if their child receives supportive care. Non-Hodgkin lymphoma was diagnosed in 35.1%, Hodgkin lymphoma in 28.1%, acute myeloid leukemia in 15.8%, chronic myeloid leukemia in 12.3%, and acute lymphoblastic leukemia in 8.8%. Cognitive development at a median age of 10.7 years was within the normal range. In subgroup analyses of children in early childhood, the gestational age at birth was correlated with the cognitive outcome at a median age of 1.7 years. Scores for language development, intelligence, attention, memory and behavior, as well as clinical neurological and general pediatric examinations were within normal ranges. In subgroup analyses, the need for supportive care in the child was associated with the loss of the mother. Prenatal exposure to hematological maternal malignancies with or without treatment did not affect the neurodevelopment of the child in the long term. Yet, caution is indicated and surveillance of the emotional development of the child is needed, especially when the mother is deceased to cancer.